74 Day case drug coated balloon only angioplasty for de novo coronary artery disease. (May 2019) - Merinopoulos, Ioannis; Wickramarachchi, Upul; Wardley, James; Khanna, Vikram; Guanawardena, Tharusha; Maart, Clint; Vassiliou, Vassilios; Eccleshall, Simon
Abstract : Introduction: The high pressures on hospital beds necessitate fast and efficient, yet safe turn-around of all elective patients ideally as day cases. Although same day discharge in patients receiving a coronary stent is widely supported by evidence, no prior study has reported on this strategy in Drug Coated Balloon (DCB) only de novo angioplasty. An important safety consideration, particularly with DCB only angioplasty is acute vessel closure due to a higher risk of coronary dissection, which will usually be apparent peri-procedurally. In this abstract we report our experience with day case DCB only angioplasty from a single high-volume UK centre and propose criteria for safe discharge. Methods: We identified all patients who underwent elective DCB angioplasty at the Norfolk and Norwich University Hospital between September 2017 and April 2018 and were discharged on the same day. Figure 1 shows our local protocol for guidance. All patients were routinely contacted via telephone post-discharge to identify any complications relating potentially to the procedure. Survival data was obtained from the Office of National Statistics. Results: 100 consecutive patients with a total of 113 de novo lesions and 10 in-stent re-stenosis lesions were included (8 patients had in-stent re-stenosis only whilst 2 had both in-stent re-stenosis and de novo disease, giving a total of 105 de novo only lesions in 92 patients). 97% of procedures were completed via the transradial route and 123 lesions were treated with 140 DCBs. The mean DCB diameter was 2.99mm while the average DCB length was 23.25mm. (See table 1 and table 2). According to the Office of National Statistics, our 30-day mortality was zero. The overall complication rate was 1%. During our follow-up telephone contact, 99 patients did not report any cardiac related symptoms necessitating urgent hospitalisation or treatment. One patient was admitted the day after the procedure with chest pain, ECG changes, and small troponin rise requiring target vessel stent implantation due to TIMI II flow. Following an uneventful recovery the patient was discharged home the next day. Retrospective review of the index procedure demonstrated a type D dissection that had not been previously appreciated due to suboptimal imaging. Conclusion: Our study confirms for the first time that day-case DCB angioplasty is safe, with zero 30-day mortality and low complication rate in an unselected population with multiple comorbidities and complex lesions. It is also cost-effective as 97 days in hospital were saved after 100 patients were treated. We have proposed a protocol for safe same day discharge but high quality imaging and appreciation of coronary dissections is of paramount importance. Conflict of Interest: None